2017
DOI: 10.1002/2017jb014045
|View full text |Cite
|
Sign up to set email alerts
|

Combining periodic hydraulic tests and surface tilt measurements to explore in situ fracture hydromechanics

Abstract: Fractured bedrock reservoirs are of socio‐economical importance, as they may be used for storage or retrieval of fluids and energy. In particular, the hydromechanical behavior of fractures needs to be understood as it has implications on flow and governs stability issues (e.g., microseismicity). Laboratory, numerical, or field experiments have brought considerable insights to this topic. Nevertheless, in situ hydromechanical experiments are relatively uncommon, mainly because of technical and instrumental limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
4
13
0
Order By: Relevance
“…7). The corresponding specific contact stiffnesses reflect the strong non-linearity of the constitutive relation; close to the equilibrium stress specific stiffness varies between 10 2 and 10 3 MPa/mm and thus falls well within the range of representative previous in-situ observations and laboratory studies (Schuite et al 2017;Zangerl et al 2008;Pyrak-Nolte and Morris 2000). When extended toward increasing fracture contact, i.e., when effective normal stresses exceed the equilibrium in-situ stresses, the stiffness of all tested fractures converge to a narrow range of 2 × 10 3 MPa/ mm to 4 × 10 3 MPa/mm.…”
Section: Specific Normal Stiffnesssupporting
confidence: 83%
See 1 more Smart Citation
“…7). The corresponding specific contact stiffnesses reflect the strong non-linearity of the constitutive relation; close to the equilibrium stress specific stiffness varies between 10 2 and 10 3 MPa/mm and thus falls well within the range of representative previous in-situ observations and laboratory studies (Schuite et al 2017;Zangerl et al 2008;Pyrak-Nolte and Morris 2000). When extended toward increasing fracture contact, i.e., when effective normal stresses exceed the equilibrium in-situ stresses, the stiffness of all tested fractures converge to a narrow range of 2 × 10 3 MPa/ mm to 4 × 10 3 MPa/mm.…”
Section: Specific Normal Stiffnesssupporting
confidence: 83%
“…The proposed hydro-mechanical model results in vastly different pressure transients depending on parameter choice and thus either group of observed transients, those with nearly constant pressures and those with continuously increasing pressure at constant flow rate, could be modeled equally well. For both pressure-transient groups, values of equilibrium aperture and equilibrium-normal stiffness parameter determined by the numerical fitting fall well within the range of previously discussed values (Klimczak et al 2010;Schuite et al 2017;Zangerl et al 2008). The different pressure transients of the two groups require distinctly different length and stiffness to match the measurement data.…”
Section: Characteristics Of Pressure Groupssupporting
confidence: 81%
“…In this context, Im et al () have recently calculated that surface tiltmeters may be suited to record deformation associated with such processes. Moreover, many authors have demonstrated that relative geodetic instruments provide useful information on the hydrogeological properties of shallower reservoirs during field hydraulic experiments (e.g., Barbour & Wyatt, ; Burbey et al, ; Schuite et al, ; Schweisinger et al, ; Svenson et al, ; Vasco et al, ). Yet the detailed behavior of surface deformation with respect to subsurface fluid flow in fractured media is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…From centimetric to metric scales, it is now broadly admitted that under certain conditions, fluid flow in fractured media can only be well understood and described using a fully coupled poromechanical modeling framework (Rutqvist & Stephansson, ). Indeed, a fracture undergoing a significant change in either pore pressure or effective stress will be deformed and this can be evidenced by laboratory experiments (Bandis et al, ; Barton et al, ; Elkoury et al, ), field tests (Cappa et al, ; Hisz et al, ; Karasaki et al, ; Schuite et al, ; Schweisinger et al, ; Svenson et al, ), or modeling (Murdoch & Germanovich, ; Schweisinger et al, ; Vinci et al, ; Wang & Cardenas, ). As their permeability is dependent on the cube of their hydraulic aperture, any opening or closing of a fracture might have a noticeable impact on the flow field (Boussinesq, ; Witherspoon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several tracer tests in dipole, convergent, and push pull configurations were performed to characterize the fracture network geometry and transport properties (Dorn et al, ; Kang et al, ; Klepikova et al, ). This site was also used to develop new hydrogeophysical methods for imaging flow and transport properties (Read et al, ; Schuite et al, ; Shakas et al, ).…”
Section: Field Setting and Experimental Setupmentioning
confidence: 99%